Novel back-reflector architecture with nanoparticle based buried light-scattering microstructures for improved solar cell performance. Issue 23 (31st May 2016) - Desta, Derese; Ram, Sanjay K.; Rizzoli, Rita; Bellettato, Michele; Summonte, Caterina; Jeppesen, Bjarke R.; Jensen, Pia B.; Tsao, Yao-Chung; Wiggers, Hartmut; Pereira, Rui N.; Balling, Peter; Larsen, Arne Nylandsted
Abstract : Light manipulation by buried light scattering microstructures in thin-film solar cells. Abstract : A new back-reflector architecture for light-management in thin-film solar cells is proposed that includes a morphologically smooth top surface with light-scattering microstructures buried within. The microstructures are pyramid shaped, fabricated on a planar reflector using TiO2 nanoparticles and subsequently covered with a layer of Si nanoparticles to obtain a flattened top surface, thus enabling growth of good quality thin-film solar cells. The optical properties of this back-reflector show high broadband haze parameter and wide angular distribution of diffuse light-scattering. The n–i–p amorphous silicon thin-film solar cells grown on such a back-reflector show enhanced light absorption resulting in improved external quantum efficiency. The benefit of the light trapping in those solar cells is evidenced by the gains in short-circuit current density and efficiency up to 15.6% and 19.3% respectively, compared to the reference flat solar cells. This improvement in the current generation in the solar cells grown on the flat-topped (buried pyramid) back-reflector is observed even when the irradiation takes place at large oblique angles of incidence. Finite-difference-time-domain simulation results of optical absorption and ideal short-circuit current density values agree well with the experimental findings. The proposed approach uses a low cost and simple fabrication technique and allows effective light manipulation by utilizing the optical properties of micro-scale structures and nanoscale constituent particles.